Fabrication of Metal Supported Solid Oxide Fuel Cells (MS-SOFC) with Ceria and Zirconia Based Electrolytes. (30th May 2017) - Toor, Sannan Yousaf; Croiset, Eric
Abstract : Metal supported solid oxide fuel cells (MS-SOFCs) were fabricated using wet ceramic processing technique. Stainless steel 430 L was characterized for porosity and electrical conductivity to be used as the porous support. D.C. polarization and Archimedes method based on ASTM Standard C373-88 were used for conductivity and porosity measurements respectively. As a benchmark, conductivity of metal support was set to be at least equal to that of anode and the porosity was kept between 35-40%. It was observed that physical properties including shrinkage behavior and CTE are two critical parameters to control during the co-sintering of metal support and electrochemical layers. A combination of inert and reducing atmosphere was also used during sintering of the cell to prohibit any oxidation of stainless steel. Cell characterization was based on visual observation (primarily cell warping or not) and scanning electron microscopy (SEM).